2007
DOI: 10.1007/s10404-007-0246-4
|View full text |Cite
|
Sign up to set email alerts
|

A numerical investigation on AC electrowetting of a droplet

Abstract: We numerically analyze the AC electric field around a droplet placed on an insulator-covered electrode. The time-averaged effective electrical wetting tension, which is a function of AC frequency, is computed by integrating the Maxwell stress. The computed wetting tension is compared with the experimental result converted from the separately obtained contact-angle data. There is a good agreement between the two results at a low-frequency range and a qualitative agreement at a high-frequency range. Interestingl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
72
0
1

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(77 citation statements)
references
References 29 publications
4
72
0
1
Order By: Relevance
“…This implies that an electrically conducting droplet will behave like a dielectric droplet at sufficiently high AC frequencies [16]. The complex capacitance can be defined using the complex permittivity as:…”
Section: Ground Electrodementioning
confidence: 99%
See 1 more Smart Citation
“…This implies that an electrically conducting droplet will behave like a dielectric droplet at sufficiently high AC frequencies [16]. The complex capacitance can be defined using the complex permittivity as:…”
Section: Ground Electrodementioning
confidence: 99%
“…Kumar et al [12] proposed a simplified RC circuit model to explain the contact angle variation of aqueous salt solutions. Hong et al [16] carried out detailed numerical modeling to predict the contact angle variation of a droplet with frequency of the AC voltage. Their numerical simulations showed that the electric field inside a droplet is very strongly dependent on the AC frequency; at a sufficiently high AC frequency, an electrically conducting droplet behaves like an insulating droplet due to the penetration of the electric field inside the droplet.…”
Section: Introductionmentioning
confidence: 99%
“…However, the present work uses a DC bias, and therefore, the liquid ribbon behaves as a perfect conductor and no electric field is present [25].…”
Section: Device Descriptionmentioning
confidence: 99%
“…A model for the display pixels hence requires accounting for the electric field distribution, as demonstrated in our earlier work (Manukyan et al 2011) and explained in the modelling paper by Oh et al (2012). Hong et al (2008), Drygiannakis et al (2009), andPooyan andPassandideh-Fard (2012) have simulated EWOD including the electric field strength in the dielectric layer and provide a thorough explanation of the numerical technique. Drygiannakis et al (2009) intention is to investigate contact angle saturation due to dielectric breakdown with this model.…”
Section: Introductionmentioning
confidence: 99%